If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -6.8 = 31 Reorder the terms: -6.8 + 3x = 31 Solving -6.8 + 3x = 31 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6.8' to each side of the equation. -6.8 + 6.8 + 3x = 31 + 6.8 Combine like terms: -6.8 + 6.8 = 0.0 0.0 + 3x = 31 + 6.8 3x = 31 + 6.8 Combine like terms: 31 + 6.8 = 37.8 3x = 37.8 Divide each side by '3'. x = 12.6 Simplifying x = 12.6
| 7d-12=38 | | 125-6x=30x+21 | | 8x^2=5x+7 | | 3/4=9/x-7 | | -2-z=4.5 | | (6-x)/(x-2)-(5x-7)/(2-x) | | 6=-8x-2 | | 114-10x=9x+19 | | 752.6-78.85= | | x+1/6=x-1/x | | 6x-5=7x+5 | | 2-5r=4-2r | | 1582/0.4 | | x+2/2x+13 | | (2q+3/3)+(3q-4/6)=q-2/2 | | a^4+9=10a^2 | | 2x*x-5x=0 | | 2q+3/3+3q-4/6=q-2/2 | | -1/4x+31/2=-5/8 | | 4/12=x+2/2x+13 | | 0=8n^2+2n | | .03w-.8(w-0.62)=40 | | 4/12=2x+13 | | -7x-18=-144 | | 2x+62=5x-7 | | 2x+6x=5x+-7 | | 2x+6z=5x-7 | | 3x-1+2x=4 | | -3(k-2)-(-6k-4)=-2 | | 49-6x=21x+19 | | 8n+25=9n | | 5n^3-10n^2+3n-6= |